Analisis Intensitas Konsumsi Energi Listrik dan Peluang Penghematan Energi Listrik pada Gedung C Kantor Sekretariat Daerah Kabupaten Semarang - Suswitaningrum, Ema; Hudallah, Noor; Putri, Riana Defi Mahadji; Sunarko, Budi (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
The use of standard AC and fluorescent lamps tends to be more wasteful. Based on observations, building C uses standard AC with a capacity that does not match the needs of the room and uses fluorescent lamps with minimal lighting intensity, so it is necessary to conserve energy to obtain opportunities for saving electrical energy while still paying attention to environmentally friendly aspects and occupant comfort. Electrical energy saving analysis is carried out through an energy audit by calculating the Energy Consumption Intensity (IKE). The pur-pose of this study is to obtain opportunities for saving electrical energy through energy conservation. Calculation of IKE values in 2019 and 2020 in building C is in the efficient category. Opportunities to save energy are carried out by replacing standard AC with low watt AC or inverter AC, resulting in savings of 28% and 30,6% with payback periods of 2,9 years and 3,8 years. Turning off the AC 15 minutes and 30 minutes before the end of working hours resulted in savings of 2,8% and 5,7% on standard AC, 2,9% and 5,8% on low watt AC and inverter AC. Energy saving opportunities by replacing fluorescent lamps with LED lamps obtained savings of 16,28% with a payback period of 4,4 years and the lighting intensity has met SNI with lighting intensity of 358-421 lux in the working room and 315-361 lux in the meeting room.